EVOLUTION AND ORIGIN OF THE MARONIA PLUTON, THRACE, GREECE - Papadopoulou, L.; Christofides, G.; Koroneos, Α.; Bröcker, M.; Soldatos, T.; Eleftheriadis, G. (Bulletin of the Geological Society of Greece, 2004)
The Maronia pluton is the youngest of the Tertiary plutons that occurred in Thrace. Three rock groups have been distinguished: a basic, an intermediate and an acid one. Based on geochemical and isotopie characteristics, the basic group probably represents a magma that isotopically equilibrated with the intermediate group at a certain point of its evolution. The evolution of the intermediate group can be described by an assimilation-fractional crystallization process (AFC). The acid group represents crustai melts that are not genetically related to the basic and intermediate groups. The emplacement of the pluton is related to post-collisional extension resulting from the subduction of the African under the European plate. The magma source of the basic and intermediate group is considered to be a LI LE- and LREE-enriched subcontinental lithospheric mantle. The acid group has probably derived by the partial melting of crustai rocks and in particular, gneiss.